Electrodeposited Co-Doped Fe3O4 Thin Films as Efficient Catalysts for the Oxygen Evolution Reaction. (20th August 2016) - Han, Shan; Liu, Suqin; Yin, Shengjie; Chen, Lei; He, Zhen
Abstract: The development of highly active electrocatalysts at a low cost is essential to the process of generating hydrogen fuel through electrochemical and photoelectrochemical water splitting. Here, we report a comprehensive investigation of the one-step electrodeposited cobalt-doped magnetite (Cox Fe3-x O4, 0 < x < 1) thin films as active and stable OER catalysts in alkaline solutions. The Cox Fe3-x O4 thin film electrode can be fabricated in minutes or even tens of seconds. The Co-doping concentration, thickness, and orientation of the Cox Fe3-x O4 films can be simply controlled by varying the deposition potential, deposition time, and the substrate, respectively. The dependences of the catalytic activity of the Cox Fe3-x O4 films on the composition, thickness, and orientation of growth are explored. The Cox Fe3-x O4 films exhibit greatly enhanced catalytic activities toward the OER compared to the Fe3 O4 thin film. The polycrystalline Cox Fe3-x O4 film deposited at −0.88 VAg/AgCl for 150 seconds exhibits the highest catalytic activity with an overpotential of ∼0.42 V at a current density of 10 mA cm −2, a Tafel slope of 53 mV dec −1, and an exchange current density of about 2.39 × 10 −10 A cm −2, which are comparable to those of Co3 O4 . Besides, the Cox Fe3-x O4 films possess good stability during the long-term electrolysis at a current density of 10 mA cm −2 in 1 M NaOH. The satisfactory catalytic activity and stability combined with the simplicity of fabrication make the electrodeposited Cox Fe3-x O4 films economically and environmentally preferable compared to Co3 O4 as catalysts for the oxygen evolution reaction.